Public health interventions in the control of emerging diseases - Bhattacharyya, Himashree; Agarwalla, Rashmi (International Journal Of Community Medicine And Public Health, 2023)
There has been an unprecedented increase in the burden of emerging diseases in the recent past. This has been attributed to changes in environment, human behavior, increased travel and human intrusion into the sylvatic cycle which has facilitated the emergence of novel and resistant strains of pathogens. A public health intervention is any effort or policy that is designed to improve mental and physical health of the population. This article focusses on the various public health interventions like vaccination, nutritional intervention, hygiene and sanitation, health awareness which has been and can contribute immensely to curb the rising threat of emerging diseases. Much research has been going on regarding the vaccines against new emerging diseases like SARS-CoV, Ebola, Lassa fever, Nipah, Chikungunya and Rift valley fever. Nutritional interventions has proven to be of much benefit in low and middle income countries because of its synergistic effect with infections. Quarantine and sanitation measures were highly effective strategies for control of COVID-19 pandemic. These preventive interventions along with a robust public health infrastructure can serve as an effective barrier in the spread of many emerging strains of diseases.